Association between interhemispheric functional connectivity (IFC) and amyloid deposition in patients with different types of dementia: Neuroimaging / imaging and genetics. (7th December 2020) - Cheung, Eva YW; Mak, Henry
Abstract: Background: Previous studies have demonstrated that accumulations of amyloid fibrils (AF) altered the cognitive performance in patients suffered from Alzheimer's disease (AD) and Mild cognitive impairment (MCI). Method: 85 participants (25 healthy controls HC, 16 AD, 21 MCI, 10 Mixed dementia (MD), 13 vascular dementia (VD) )were recruited to undergo Resting state functional MRI (rs‐fMRI) scanning and 18F‐Flutemetamol Positron Emission Tompography Computed Tomography (PETCT) scanning. Voxel Mirrored Homotopic Connectivity (VMHC) was calculated based on the method used by Kelly et al 2011 [1] and Zuo et al 2010 [2]. Standardized uptake value (SUV) were recorded from the PET images. With reference to the SUV of pons, SUV ratio (SUVR) were obtained. Association between IFC and SUVR were calculated based on the Spearman's correlation test. Result: IFC was negatively associated with SUV in AD at lingual gyrus (r=‐0.552, p=0.027) and cuneus (r=‐0.609, p=0.012) within visual network, VN; and MCI in Inferior frontal gyrus (IFG) triangular (r=‐0.488, p=0.02) within default mode network (DMN). For MD, IFC was positively associated with SUVR at angular gyrus (r=0.662, p =0.037), middle frontal gyrus (r=0.817, p =0.004), superior frontal gyrus (r=0.669, p =0.035) within DMN; at middle temporal gyrus MTG (r=0.554, p =0.049), Middle frontal gyrus orbital (r=0.742, p =0.014) within central executive network (CEN); at supplementary motor area, SMA (r=0.654, p =0.040) within sensory motor network (SMN); at IFG orbital (r=0.856, p =0.002) within dorsal attention network (DAN). For VD, IFC was positively associated with SUVR at posterior cingulate (r=0.611, p =0.026) within DMN; at middle temporal gyrus (r=0.563, p =0.045), rolandic operator (r=0.603, p =0.029), Precentral Gyrus (r=0.554, p =0.049) and Posterior central gyrus (r=0.653, p =0.019) within CEN; inferior temporal gyrus (r=0.605, p =0.028) within DAN. Conclusion: The findings demonstrated the accumulation of AF decreases IFC in VN for AD and SRN for MCI. While for MD and VD, accumulation of AF increases with the IFC in DMN, CEN, SMN and DAN, suggesting that there is compensation of brain function, through recruiting other networks for non‐amyloid dominant dementia.